2012
DOI: 10.1371/journal.pone.0044440
|View full text |Cite
|
Sign up to set email alerts
|

Increased RhoA Prenylation in the loechrig (loe) Mutant Leads to Progressive Neurodegeneration

Abstract: The Drosophila mutant loechrig (loe) shows age-dependent degeneration of the nervous system and is caused by the loss of a neuronal isoform of the AMP-activated protein kinase (AMPK) γ-subunit (also known as SNF4Aγ). The trimeric AMPK complex is activated by low energy levels and metabolic insults and regulates multiple important signal pathways that control cell metabolism. A well-known downstream target of AMPK is hydroxyl-methylglutaryl-CoA reductase (HMGR), a key enzyme in isoprenoid synthesis, and we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…5A), we reduced activity of Drosophila orthologs of Farnesyl Pyrophosphate Synthase (FPPS) and geranylgeranyl diphosphate synthase (GGPS) and examined toxic levels of trametinib or everolimus. The FPPS mutant fpps k03514 , previously demonstrated to decrease levels of Rho prenylation (Cook et al 2012), was strongly insensitive to trametinib toxicity and mildly insensitive to everolimus toxicity (Fig. 7B,C).…”
Section: Resultsmentioning
confidence: 68%
“…5A), we reduced activity of Drosophila orthologs of Farnesyl Pyrophosphate Synthase (FPPS) and geranylgeranyl diphosphate synthase (GGPS) and examined toxic levels of trametinib or everolimus. The FPPS mutant fpps k03514 , previously demonstrated to decrease levels of Rho prenylation (Cook et al 2012), was strongly insensitive to trametinib toxicity and mildly insensitive to everolimus toxicity (Fig. 7B,C).…”
Section: Resultsmentioning
confidence: 68%
“…We previously showed that loe mutant flies show increased prenylation and genetically interact with RhoA, whereby reducing RhoA levels suppressed loe -induced phenotypes [14]. Rho GTPases are key regulators of the actin network through their downstream targets PAK and ROCK [17].…”
Section: Discussionmentioning
confidence: 99%
“…Well-known targets of isoprenylation are small GTPases, like Ras, Rab, Rac, and Rho, which through the addition of these lipid moieties can associate with membranes and subsequently be activated [13]. The connection between loe and the isoprenoid pathway was confirmed by experiments showing that altering isoprenoid levels, either genetically or by pharmacological means, affected the severity of loe associated phenotypes and loe flies show increased levels of isoprenylated RhoA [14]. In addition, increased RhoA levels enhanced the degeneration observed in loe , whereas decreased amounts suppressed it.…”
Section: Introductionmentioning
confidence: 95%
“…This reduced AMPK function allows adult flies to develop past the earlier lethality found in AMPK-null mutations, but results in a severe vacuolar pathology and widespread neuronal death in the adult fly brain (Kazgan et al 2010; Tschape et al 2002). More recently, Kretzschmar and colleagues have demonstrated that loe mutants have increased prenylation of Rho1 (Rho1 is orthologous to mammalian RhoA) (Cook et al 2012). Although loechrig does not model the etiology of AD, Cook et al stress the translational value of their research by discussing the link between activated RhoA/Rho-associated protein kinase (ROCK) signaling and AD (Cook et al 2012).…”
Section: 2 Selected Disease Models Studied In Drosophilamentioning
confidence: 99%